Parental Divorce and Sibling Relationship in Nyakambu Village Southern Division Kabale District - Comfort Kukundakwe (Uganda Christian University, 2024)
This study focused on the topic “parental divorce and sibling relationship in Nyakambu village, Southern division Kabale municipality and it was guide by three main objectives which included to explore the nature of sibling relationships after divorce of parents, to determine the coping strategies employed by siblings to navigate emotional challenges and to examine the connection between parental divorce and quality of sibling relationship. The study was carried out using the cross-sectional research design where the quantitative research approach was utilized. Questionnaires were used to collect data from siblings whereas interviews were conducted with the parents regarding the topic. The study found that most of the siblings whose parents have gone through divorce or are going through divorce offer emotional support to each other which has brought them closer than even before, improved their communication and that siblings can now share their challenges. It was also discovered that in some families were the parents have divorced or are going through divorce, there is increased conflicts am siblings as they compete for attention from parents. It was also discovered that some siblings have been able to navigate challenges that come with parental divorce due to the support from their parents and through the interviews we found out that siblings who had more attention from parents their relationship was less affected by parental divorce compared to those who didn’t have support from parents. Some recommendations were made where l encouraged all the parents to always work together and be available in the lives of their children even after divorce to provide emotional support and stability even if they are not together as well l call upon all the parents to create a safe space for the children to express their emotions and concerns which helps them to process their feelings and build stronger bonds with their siblings and encouraged parents to help these children access professionals like counselors, therapists, and social workers for counseling services to support children struggling to cope with parental divorce to help them develop healthy emotional regulation strategies hence helping them navigate the different stress that come with divorce then ended my dissertation with a conclusion.